Comparative Study of the Combined Supersonic Separator and Vortex Tube Performance for Hydrocarbon Gas Drying. Issue 4 (3rd March 2021) - Yudakov, Alexandr; Vlasenko, Victor; Slesarenko, Vyacheslav
Abstract: Experimental investigation of the combined supersonic separator (CSS) characteristics was carried out and the results were compared with those from the vortex tube. The separator is a counter‐flow vortex tube with an energy separation chamber in the shape of a Laval nozzle; it can be used for hydrocarbon gas transportation preparation and power plant fuel gas drying. Numerical modeling was carried out to confirm the flow specifics in the examined separator structure. Although the cooling capability of the CSS is 30–50 % less than that of the vortex tube, its efficiency of moisture removal is twice as large, as is shown by the experimental research. The maximal cooling power corresponds to a cold flow fraction level of 0.39, while the range of optimal values for the moisture separation is 0.4–0.6. Abstract : The separation efficiency of a combined supersonic separator (CSS) is much higher than that of a three‐flow vortex tube (TVT) for a cold flow share ( μ ) of > 0.3. In this case, the maximum cooling of the cold flow was achieved at μ = 0.37. Optimal modes for separation are in the cold flow share range of 0.50–0.60, despite the fact that the thermal efficiency of the CSS is lower than that of the TVT.